Newly Identified Fragments of 4Q51 (4QSama) - Ableman, Oren Shalom (2023)
The following paper is a preliminary publication of newly identified fragments of the book of Samuel that all belong to manuscript 4Q51. The fragments were discovered during the cataloging effort being carried out by the Israel Antiquities Authority (IAA) as part of the digitization project of the Leon Levy Dead Sea Scrolls Digital Library (www.deadseascrolls.org.il). Some of the fragments that will be presented were published in the past, but with various errors. Other fragments have never been published, although due to the placement of some of them on the museum plates it is clear that someone in the past recognized that they belong to 4Q51.
Keywords: Biblical Manuscripts; multispectral imaging; Lucianic text; Textual Criticism; Samuel scroll (4Q51); 4Q51